Comparative Study between Islamic Law and International Law on the Purposes of Peace - Zainul Muballighin (Trigin Publisher, 2022)
Islam was born not just as a belief system, but also because Islam was born because of a system of social norms framed through peace. Therefore the idea of ​​peace in Islam is related to the vertical relationship between hablum minallah and horizontally hablum minannas. Likewise with international law, the goal of peace in international law was born not because of a social contract (state/organization), but the goal of peace in international law was born as a logical consequence of the social contract system. Based on the explanation above, the authors assume that the issue of peace is very interesting to be used as a scientific work (thesis). in compiling this thesis, the authors provide the title (Comparative Study Between Islamic Law and International Law Concerning the Purposes of Peace). The conclusion of the results of the analysis in this thesis, there are similarities and differences in the goals of peace in Islamic law and international law. The similarity is that the recommendations for peace are not limited to individuals, groups, even gender and they both want to create a safe situation without any violence, conflict, conflict, and war, both culturally and structurally. Meanwhile, the difference is that in Islamic law, peace is born because of religious advice and psychological needs. Meanwhile, international law was born peaceful because it wanted to create a world order that is safe without any violence and war.